EFFECTS OF PLASTIC SURGERY ON HUMAN HEALTH - Turayeva Malika Shokirovna (Web of Journals Publishing, 2024)
This article presents the opinions of domestic and foreign scientists about modern methods of plastic surgery. In order to satisfy cosmetic and reconstructive demands, modern plastic surgery procedures have greatly advanced, becoming safer, more effective, and less intrusive. Modern cosmetic surgery procedures have changed dramatically, combining cutting-edge medical technology with sophisticated approaches to enhance patient happiness, safety, and results.
Keywords: Modern plastic surgery utilizes, Endoscopic Surgery, Laser Surgery, Ultrasound Assisted Liposuction (UAL), 3D imaging and computer assisted design (CAD), Breast Augmentation, Burn Reconstruction, hyaluronic acid, collagen stimulators, breast augmentation, facial rejuvenation.